1985
DOI: 10.1177/001316448504500308
|View full text |Cite
|
Sign up to set email alerts
|

Children's Interests Inventory, Grades 4–6

Abstract: A factored interest inventory for children was developed from interest items obtained from literature review and an open-ended questionnaire, the Preliminary Children's Interest Inventory, administered to children, parents, and teachers. These items, collapsed to form a 121 item Children's Interest Inventory, were rated on a 5-point like-dislike scale by 517 children in grades four, five, and six from Marshalltown, Iowa. Teachers rated each child's scholastic, social, and creative ability. Factor analyses show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…A focus on familiar activities, rather than unfamiliar occupations, appears to be a better means of assessing interests. In research in which interests have been assessed through familiar activities, the structure of interests in children has been found to differ from that of adults (Dusek, Kermis, & Monge, 1979; Freeberg & Rock, 1973; Tyler, 1955, 1956; Zbaracki, Clark, & Wolins, 1985).…”
Section: Interest Assessment In Childrenmentioning
confidence: 99%
“…A focus on familiar activities, rather than unfamiliar occupations, appears to be a better means of assessing interests. In research in which interests have been assessed through familiar activities, the structure of interests in children has been found to differ from that of adults (Dusek, Kermis, & Monge, 1979; Freeberg & Rock, 1973; Tyler, 1955, 1956; Zbaracki, Clark, & Wolins, 1985).…”
Section: Interest Assessment In Childrenmentioning
confidence: 99%
“…. The few studies that attempted to assess the domain of interests more completely (Dusek, Kermis, & Monge, 1979;Tyler, 1955Tyler, , 1956Zbaracki, Clark, & Wolins, 1985) found that although there was some similarity, the structure of interests for children differed from that for adults.…”
mentioning
confidence: 99%
“…Some other researchers assessed children’s interests using only a very narrow band, not representative of a broader domain of interests (e.g., Fouad & Smith, 1996; Roberts & Petersen, 1992; Schulenberg et al, 1991). The few studies that attempted to assess the domain of interests more completely (Dusek, Kermis, & Monge, 1979; Tyler, 1955, 1956; Zbaracki, Clark, & Wolins, 1985) found that although there was some similarity, the structure of interests for children differed from that for adults.…”
mentioning
confidence: 99%
“…Varios investigadores han encontrado factores de intereses en niños y niñas de primer grado en adelante (Cirino Gerena, 2013;Tracey, 2001;Tyler, 1955;Zbaracki, Clark, & Wolins, 1985). Estos factores evidencian que la estructura del universo de los intereses comienza a definirse en la niñez, por lo que conviene tomar teorías que discutan el origen y desarrollo de los intereses a partir de esta.…”
Section: Towards a Universal Model Of Interestsunclassified